Ukraine : Request for Purchase under the Rapid Financing Instrument and Cancellation of Stand-by Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report, 2022)
While geopolitical tensions with Russia had already curtailed Ukraine's access to markets, the escalation to an invasion of Ukraine by Russia and full-blown war on February 24 has dramatically altered Ukraine's outlook. A deep recession and large reconstruction costs are to be expected, on the backdrop of a humanitarian crisis. With the war ongoing, the situation remains extremely fluid, and any forecast is at this stage subject to massive uncertainty. The authorities are rightly focusing on ensuring the continuity of critical government operations, preserving financial stability and protecting priority spending.